Profitability of broiler contract farming: a case study in Johor and Sabah - Md Isa, Abu Hassan; Ismail, Mohd Mansor; Samsuddin, Nur Syahirah; Abdurofi, Ilmas (Universiti Malaysia Sarawak, 2019)
The study evaluated the profitability of small scale broiler production in Sabah and Johor with emphasis on contract farming. Cost benefit analysis and financial appraisal were carried out and the net return, value of input and output indicated broiler contract farming in Johor was more viable and profitable compared to Sabah. There were two obstacles limiting sustainable broiler contract farming in Sabah: 1) higher feed cost, and 2) low profit due to low gross margin between production cost and the ex-farm selling price. Therefore, in this study, the financial performance was evaluated, and sensitivity analysis was performed to assess the effect of changes in feed cost and selling price. The results concluded that Sabah broiler contract farming was more sensitive to changes in feed cost and selling price while the implementation of a zero tax incentive to small scale broiler contract farmers especially in Sabah would help the industry remained sustainable.